Exploring Interactive Multimedia In Literal Reading Class - Khoiriyah Khoiriyah; Sulistiyani Sulistiyani; Agung Wicaksono; Mahendra Puji Permana Aji (STKIP PGRI Tulungagung, 2021)
The aim of this study was to investigate the impact of interactive multimedia to students’ reading comprehension at Literal Reading class. All participants were conveniently selected from the first year students of English Language Education Department at Nusantara PGRI Kediri University. Thirthy participants were assigned as a sample. Quantitative method and experimental approach with One-Group Pretest-Post design were applied in this present study. Data collection through pre-test and post- test. Pre-test was administered before treatment, while post-test was administered after treatment. After gaining the data, t- test was analyzed using SPSS 23. The analyzes resulted in the finding that there was a significant difference score in pre- test and post-test. The mean score of post-test was better than pre-test. Thus, it can be said that interactive multimedia can impact the students’ reading comprehension of the first year of English Language Education Department at Nusantara PGRI Kediri University.